The potential use of boron containing resources for protection against nuclear radiation. (November 2021) - Dong, Mengge; Zhou, Suying; Xue, Xiangxin; Feng, Xiating; Sayyed, M.I.; Khandaker, Mayeen Uddin; Bradley, D.A.
Abstract: Recognizing the large neutron capture cross section of boron, the suitability of boron containing resources are studied for protection against nuclear radiation. Experimental and simulation study for neutron (thermal and fast) and gamma-ray shielding features of six different types of boron containing natural materials, obtained from the utilization process of boron ores in Liaoning Province of China, are performed here. Shielding ability of B1-B6 for thermal neutron is mainly based on the on the absorption cross section of boron; The elements with higher content or cross section have higher contribution for the fast neutron shielding; The interactions of B1-B6 with gamma rays are different with each other because of the difference components, but the mainly are Photoelectric Absorption in the low energy region, Incoherent Scattering in the intermediate energy region and Pair Production in nuclear filed in the high energy region, the elements with higher content or high atomic number show higher contribution for the shielding performance. The neutron and gamma ray shielding show a positive correlation with the boron content and material density, respectively. Comprehensive shielding performance of the studied samples is found to be better than some commercial materials. Overall, the composites prepared by boron containing resources and epoxy resin show excellent shielding performances for neutron but poor for gamma rays. Particularly, the boron rich slag shows the greater performance for both neutron and gamma ray shielding. The obtained results show the pathway for potential use of boron containing resources as structural materials in the radiation environment, and provide protection to both radiation worker and general populace from harmful nuclear radiation. Highlights: Neutron shielding features depend on elements with higher content and cross section. Gamma ray shielding depends on the element with higher content and atomic number. Shielding properties of B1-B6 are better than some other commercial materials. Boron rich slag is the best one for both neutron and gamma ray shielding.